PENERAPAN KONSEP ZERO DELTA RUNOFF DENGAN TEKNOLOGI EKODRAINASE PADA ARIA REMPOA TOWNHOUSE, TANGERANG SELATAN - Andajani, Sih; Haryadi, Tania Diva; Hidayat, Dina P.A; Sejati, Wahyu; Kurniyaningrum, Endah (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2024)
The increasing need for basic urban facilities and infrastructure, such as housing, can result in a reduction in green open land which can reduce the ability of water to infiltrate into the ground and increase surface runoff. Aria Rempoa Townhouse, a housing complex that is still in the development process, may have problems like these. Therefore, it is necessary to implement the zero delta runoff concept with ecodrainage technology such as retention pond and infiltration well. Research was carried out on the design flood at the outlet before the townhouse is built and after the townhouse is built if the zero delta runoff concept is applied with retention pond and infiltration wells. There are 3 scenarios, scenario 0 before the townhouse is built, scenario 1 after it is built without ecodrainage technology, scenario 2 after it is built with a retention pond, and scenario 3 after it is built with infiltration wells. The research results show that scenario 2 fulfills the concept of zero delta runoff with a pool area of 42 m2 with a depth 3.5 m and 2 outlet pipes with diameter 10 inches without doors discharge the design flood at the outlet of 0,281 m3/sec which is smaller than design flood at the outlet before the townhouse is built of 0.288 m3/second.